A behavioural audit as a tool of the Health and Safety Management Systems - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2009)
In the article there were presented general assumptions concerning employees’ hazardous behaviour modification programme with use of a behavioural audit. The author depicted a method of the audit conduct underlining the meaning of a dialogue with an employee for proper identification of reasons for hazardous behaviours. Therefore, a crucial role of auditors’ selection and training was emphasised for they deliver data for further analysis. The quality of data obtained in the behaviour and work conditions observation process is vital for the programme success. Consequently, periodic trainings for behavioural auditors need to be carried out to deepen their knowledge and improve the methods of auditing.